Four new species of Desmopachria Babington (Insecta, Coleoptera, Dytiscidae) from the Amazon river floodplain - Braga, Rafael Benzi; Ferreira-Jr, Nelson (Zootaxa, 2010)
Four new species of Desmopachria from the Amazon river floodplain (várzea) are described and illustrated, D. manus sp. nov., D. varzeana sp. nov., D. cavia sp. nov. and D. nigrocapitata sp. nov., together with new distributional records of D. balionata Miller, D. draco Miller, D. subnotata Sharp and D. striola Zimmermann for Amazonas and Pará states in Brazil.